Trees nurture nutrition: An insight on how to integrate locally available food tree and crop species in school gardens - McMullin, S.; Stadlmayr, B.; Ngethe, E.; Wekesa, B.; Njogu, K.; Gachuiri, A.; Mbaya, B.; Katiwa, A.; Jamnadass, Ramni H. (Routledge, 2020)
Neglected indigenous fruit trees have an important role in providing vital minerals and micronutrients to growing children, as well as the wider community. The diversity of indigenous fruit trees also means they have an important role to play in addressing seasonality and hunger periods facing many rural communities by ensuring the availability of nutritious fruits for a healthy diet year-round. This chapter will highlight the diversity of indigenous fruit trees and their food composition and contribution to micronutrient and wider dietary needs. It will also highlight the ‘portfolio approach’ – for addressing seasonal and nutrient specific gaps in local diets. School gardens offer an important entry point for the integration and promotion of indigenous fruit trees for nutrition education and promotion of healthy diets. Schools also offer a platform for wider community engagement by promoting practical learning and engagement not only of pupils through such programmes as 4K clubs but also community and parent learning through SMCs and champion farmers.